2022
DOI: 10.1007/s00590-022-03325-9
|View full text |Cite
|
Sign up to set email alerts
|

Distal radius malunion: outcomes following an ulnar shortening osteotomy

Abstract: Purpose Positive ulnar variance following a distal radius malunion can lead to ulnar-sided wrist pain, loss of grip strength, and distal radioulnar joint impingement. The primary aim of this study is to describe upper limb-specific functional outcomes following ulnar shortening osteotomy (USO) for ulnar-sided wrist pain associated with malunion of the distal radius. Methods We retrospectively identified 40 adult patients from a single centre over a 9-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Huddleston et al showed that fixating the radius in -4 mm of ulnar negativity significantly decreased radial translation after sectioning the volar radioulnar ligament and triangular fibrocartilage complex (TFCC) [20]. Similar evidence reported that positive ulnar variance one year after distal radial fracture was clearly associated with unfavorable DASH score and weakness of grip [21,22].…”
Section: Resultsmentioning
confidence: 88%
“…Huddleston et al showed that fixating the radius in -4 mm of ulnar negativity significantly decreased radial translation after sectioning the volar radioulnar ligament and triangular fibrocartilage complex (TFCC) [20]. Similar evidence reported that positive ulnar variance one year after distal radial fracture was clearly associated with unfavorable DASH score and weakness of grip [21,22].…”
Section: Resultsmentioning
confidence: 88%
“…Although some conservatively treated distal radial fractures result in malunion ( Brogren et al., 2011 ; Katt et al., 2020 ; Ng and McQueen, 2011 ), the incidence of symptomatic malunion is not well reported. When a malunited distal radial fracture with radial shortening leads to symptomatic ulnar impaction causing ulnar pain, an ulnar shortening osteotomy can be considered a treatment choice, but is less common than radial osteotomy ( Hassan et al., 2019 ; Stirling et al., 2023 ; Terzis et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NPS or FFT has been used in several orthopedic studies to measure patient satisfaction after a procedure and has been found to be a useful addition to traditional measures of patient satisfaction. 12–19 According to Stirling et al, the FFT correlated well with postoperative hand surgery functional improvement and patient satisfaction. 12 The benefits of using the NPS in healthcare includes ease of use, high completion rates, 13 and being well understood by most patients.…”
Section: Introductionmentioning
confidence: 99%